In vitro anti-atherogenic effects of asiatic acid in human aortic endothelial cells - Fong, Lai Yen (2016)
In early pre-lesional stage of atherosclerosis, endothelial cell activation is characterized by increased endothelial permeability, increased expression of cell adhesion molecules (CAMs), leukocyte adhesion and migration across the endothelium. Asiatic acid is a major triterpene isolated from Centella asiatica (L.) Urban and it has been shown to possess anti-oxidant, hypolipidemia and anti-inflammatory activities. This study aimed to investigate protective effects of asiatic acid on TNF-α-induced early atherogenic events, in the context of endothelial cell activation, using human aortic endothelial cells (HAECs). Fluorescein isothiocyanate (FITC)-dextran permeability assay, U937 monocyte adhesion and migration assays were examined using fluorescence-based methods. The levels of soluble CAMs were measured using multiplex kits and flow cytometry. Localization of filamentous (F)-actin, diphosphorylated myosin light chain (diphospho-MLC), adherens junctions (AJs) and tight junctions (TJs) in cells were investigated using immunocytochemistry and confocal microscopy. Total protein expression of CAMs, diphospho-MLC, vascular endothelial (VE)-cadherin, β-catenin, occludin, zona occludens (ZO)-1 and phosphorylated inhibitors of κB (p-IκB-α) were determined using western blot analysis. The expression of AJ and TJ proteins in membrane, cytosolic and cytoskeleton fractions were also determined using western blot analysis. Asiatic acid significantly suppressed TNF-α-induced endothelial hyperpermeability, but did not reduce the increased monocyte adhesion and migration. Asiatic acid also inhibited VCAM-1 expression and production of soluble CAMs (sEselectin, sICAM-1, sVCAM-1 and sPECAM-1). Besides, asiatic acid prevented TNF-α- induced redistribution of F-actin but failed to alter the increased F/G actin ratio. By using cytochalasin D, an actin depolymerizing agent, asiatic acid was demonstrated to stabilize peripheral F-actin filaments. Yet, asiatic acid did not improve cytochalasin Dinduced increased permeability. Furthermore, asiatic acid localized diphospho-MLC filaments at the cell periphery and significantly augmented TNF-α-induced increased MLC diphosphorylation. Asiatic acid also prevented TNF-α-induced reticular AJ disruption by enhancing junctional areas covered by VE-cadherin and β-catenin. This protective effect was found to be independent of changes in either total amount or intracellular redistribution of VE-cadherin and β-catenin. For TJs, confocal imaging showed that asiatic acid opposed TNF-α-induced loss of ZO-1 from the cell borders. However, asiatic acid did not alter both total occludin and ZO-1 expressions in whole cell lysate. Subcellular fractionation demonstrated that asiatic acid inhibited TNF-α- induced ZO-1 internalization from membrane to cytoplasm and occludin redistribution from cytoplasm to cytoskeleton. In addition, asiatic acid suppressed TNF-α-induced phosphorylation of IκB-α. These results suggest that asiatic acid protects against TNF- α-induced endothelial barrier disruption and reduces the release of soluble CAMs, which are important biomarkers for the risk prediction of cardiovascular diseases. Asiatic acid also stabilizes the cytoskeleton by localizing peripheral F-actin and diphospho-MLC filaments. However, the actin stabilization is not essential for barrier protective effect of asiatic acid. The barrier stabilizing effect of asiatic acid is found concomitant with enhancement of reticular AJ formation, inhibition of TJ redistribution and suppression of NF-κB activation. In conclusion, a novel protective role of asiatic acid in TNF-α-induced endothelial barrier dysfunction was demonstrated. This reveals new therapeutic usage of asiatic acid in the prevention of early atherosclerosis, which involves endothelial activation.